Pelatihan Pembuatan Media Presentasi Multimedia Pembelajaran IPAS Berbasis Artificial Intelligence di MI Muhammadiyah - Nurfadliah Nurfadliah; Andi Marsyanawiah; Ikhlas Ul Aqmal (Universitas Negeri Gorontalo, 2026)
The rapid development of digital technology has encouraged the integration of Artificial Intelligence (AI) in education, including the development of multimedia learning media. However, many teachers still have limited skills in utilizing AI-based technology in the learning process. This community service activity aimed to improve teachers’ skills in developing AI-based multimedia presentation media for IPAS learning at MI Muhammadiyah Kota Utara, Gorontalo. The methods used included preparation, training implementation, practice sessions, and evaluation. The activity involved 20 teachers through material presentations, discussions, and direct practice using AI applications. The results showed that teachers gained new knowledge and skills in creating interactive and innovative learning media. Teachers also showed high enthusiasm and active participation during the training. The implementation of AI-based multimedia learning media is expected to improve learning quality, student motivation, and teachers’ digital competencies in the digital era.